Pain and Treatment - Racz, Gabor B.; Noe, Carl E. (IntechOpen, 2014)
This new edition reflects the evolution of the field including new topics for historical relevance regarding the changing attitudes towards opioid prescription and use. The book points out that the realization of liberalizing use is almost uncontrollably linked to unnecessary patient death. Similarly, the evidence is increasingly confirming that interventional pain procedures work. New evidence presents, for example, that Percutaneous Lysis of Adhesions is an effective therapeutic modality that has advantages over other options due to its cost effective nature and long term outcomes reducing the need for additional procedures including surgeries and more and more expensive medications. Awareness about the consequences of bad outcomes leads to medicolegal complications. The inevitable trigger is bad outcome which is often related to knowledge, training, experience, as well as equipment design. Some of the examples and lessons learned from the medicolegal arena may soon prevent such occurrences.